2013
DOI: 10.1155/2013/853083
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Adverse Events Reported during the First Ten Years (1998–2008) after Introduction in the State of Rondonia, Brazil

Abstract: Despite good safety records, vaccines given to young children can cause adverse events. We investigated the reported adverse events following immunization (AEFI) of vaccines given to children of less than seven years of age during the first ten years (1998 to 2008) in the state of Rondonia, Brazil. We worked with the events related to BCG (Bacillus Calmett-Guérin), HB (hepatitis B), DTwP/Hib (diphtheria-tetanus-pertussis+Hemophillus influenza b), DTP (diphtheria-tetanus-pertussis), MMR (mumps, measles, rubella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
1
17
0
6
Order By: Relevance
“…This was similar to reports from passive surveillance systems in the US (VAERS-Vaccine Adverse Events Reporting System) 26 and other countries 27, 28 . Consistent with findings from prior surveys, our study demonstrates parental misunderstanding of the definition of fever threshold, as one-fifth of participants who measured the temperature considered readings of ≤ 100 °F (37.8 °C) to correspond to fever in the child.…”
Section: Discussionsupporting
confidence: 87%
“…This was similar to reports from passive surveillance systems in the US (VAERS-Vaccine Adverse Events Reporting System) 26 and other countries 27, 28 . Consistent with findings from prior surveys, our study demonstrates parental misunderstanding of the definition of fever threshold, as one-fifth of participants who measured the temperature considered readings of ≤ 100 °F (37.8 °C) to correspond to fever in the child.…”
Section: Discussionsupporting
confidence: 87%
“…A group of data about HepB AEs summarized through a large database of reported adverse events following immunization (AEFI) during 10 years in Rondonia (a state of Brazil) is nearly to us. 29 Practical significance in this study can be regarded as the dominant aim. 10 mg HepB-HPY as a new vaccine for infants was firstly applied in Ningbo, China and also as a unique kind of HepB is supported by government which would be administrated to about 80,000 newborns every year.…”
Section: Discussionmentioning
confidence: 98%
“…Immunization of infants and young children against serious infectious diseases is the most successful and cost-effective intervention in preventative health care [1, 2]. However, vaccination occasionally leads to undesirable effects including adverse reactions that are referred to as adverse events following immunization (AEFI) [3].…”
Section: Introductionmentioning
confidence: 99%
“…53% of all WHO member countries reported having a national AEFI monitoring system [9]. Previous studies have demonstrated the importance of vaccine safety surveillance [5, 10, 11] though such surveillance and follow-up infrastructure lags behind vaccine development in industrialized countries and is absent in most developing countries including Kenya [1]. …”
Section: Introductionmentioning
confidence: 99%